Review: Third Annual Bronze Casting Festival, Uelsen (DE) - E. Giovanna Fregni (EXARC, 2019)
The third annual Bronze Casting Festival at the Bronzezeithof in Uelsen continued its theme of metalworking and experimental archaeology in a Bronze Age setting. The event drew participants from around Europe and the US to combine their knowledge and share experiences.